STRATEGI PENGAJARAN BAHASA INDONESIA PADA SEKOLAH MENENGAH PERTAMA DI KABUPATEN KLATEN - Aji, Wisnu Nugroho; Budiyono, Sri (JURNAL PESONA, 2018)
AbstractThis is the follow-up study which is done by the researchers previously. The researchers focus on the implementation of Curriculum 2013 in Bahasa Indonesia subject of Junior High School in Klaten Regency. From the result of that, it is known that one obstacle faced by the Bahasa Indonesia teacher in implementing Curriculum 2013 is learning strategy. Based on the problem above, this study focuses on the Bahasa Indonesia learning strategy by taking the population of Junior High School in Klaten Regency. The aim of this study is to describe the language learning plan and strategy in of Junior High School in Klaten Regency. This research design in this study is case study. From the data analysis, it can be seen that Bahasa Indonesiaâs teacher of Junior High School in Klaten Regency used conventional strategy (indirect) and it is not relevant to the Curriculum 2013. Those strategies are as follow (1)Classical Learning Strategy;(2)Indirect Learning Strategy; and (3)Heuristic Learning Strategy.Keywords: Learning Strategy, Bahasa Indonesia, Curriculum 2013